Joyce's Mandala - O'Shea, Colm (Trinity College (Dublin, Ireland). School of English, 2005)
The term "mandala" is a Sanskrit word which can be translated as meaning "sacred circle". The "circle" in this instance typically encloses a highly structured icon which represents a microcosm of the universe and/or consciousness. Today, mandalas are produced by a variety of people from a multitude of backgrounds but these sacred circles were originally constructed by spiritually adept artists from aboriginal cultures in order to represent the experience of subject-object dissolution or even to help actively initiate such a dissolution. Indian and Oriental civilisations developed this spiritual-artistic practice to its zenith in terms of technical sophistication; here multitudes of icons within the design create layers upon layers of esoteric meaning for both the mandala artist and the spectator.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin